The Influence of the Amount of Credit Disbursement on Profitability in State-Owned Banking in Indonesia - Fatichatur Rachmaniyah; Khusmayasari, Dewi; Abdul Hadi; Siti Makhmudah (Basic and Applied Accounting Research Journal, 2023)
This research aims to determine the effect of the amount of credit disbursement on profitability at state-owned banks in Indonesia. This research uses quantitative methods with simple linear regression analysis. The object of this research is state-owned banks listed on the IDX in the 2019-2021 period. By using secondary data from quarterly financial reports in 2019-2021. The results of this research are that the amount of credit disbursement significantly positively affects banking profitability